Deglycosylated azithromycin alleviates cisplatin-evoked constipation in mice by altering host metabolome and gut microbiota composition - Xiaoting Gu; Shuwen Zhu; Shuwen Zhu; Weixue Tian; Xiaohe Li; Yutian Cai; Yutian Cai; Chaoyue Zheng; Chaoyue Zheng; Xiang Xu; Xiang Xu; Conglu Zhao; et al. (Frontiers in Microbiology)
IntroductionChemotherapy induced constipation (CIC) is a gastrointestinal side effect that occurs in patients receiving chemotherapy, which can further deteriorate the living quality of cancer patients. Deglycosylated azithromycin (Deg-AZM), a newly developed Class I drug with good therapeutic effects on chronic constipation, has been approved for clinical trials in 2024. However, it is unclear whether Deg-AZM has any impact on gut microbiota of CIC mice. The purpose of this study was to explore the role of Deg-AZM in treating CIC by modulating the gut microbiota.MethodsThe therapeutic effects of Deg-AZM on intestinal motility were assessed in a cisplatin-induced CIC mouse model. The gut microbiota composition was analyzed using 16S rRNA sequencing, and metabolic changes were evaluated through untargeted metabolomics of fecal samples.ResultsDeg-AZM significantly enhanced intestinal motility in the mice with cisplatin-evoked constipation. Gut microbiota analysis revealed that Deg-AZM altered the community composition by decreasing Deferribacterota and Pseudomonadota and increasing Bacteroidota, Lactobacillus and Muribaculaceae. The feces metabolomics revealed that alanine, aspartate and glutamate metabolism, citrate cycle (TCA cycle), purine metabolism, primary bile acid biosynthesis and taurine and hypotaurine metabolism in CIC model were modulated by Deg-AZM.ConclusionDeg-AZM could alleviate cisplatin-evoked constipation in mice by reshaping the structure of gut microbial community, which may provide a potential basis for the use and clinical development of Deg-AZM for CIC treatment.